Analisis Risiko Kredit Perbankan Go Public di Indonesia: Suatu Perspektif Makro Ekonomi - Tasman, Abel (Jurnal Kajian Manajemen Bisnis, 2015)
The aims of  this study is to analyze the influence of  macroeconomics variable consist of interest rate, the growth of Gross Domestic Product (GDP) and inflation rate on credit risk . This study is focused on banking companies listed on Indonesian Stock Exchange from 2009-2013. The method of data collection is purposive sampling. There are 125 datas in this  observation during five years. This study used secondary data from Indonesian Stock Exchange (IDX) and Indonesian Capital Market Directory (ICMD)  with multiple regression as statistical tool. This study shows that interest rate has negative and insignificant effect on the credit risk, the growth of GDP has negative and significant effect on the credit risk and inflation rate has positive and significant effect on the credit risk.